Pemberdayaan Usaha Tani Tembakau Di Dusun Kedung Sumur Desa Jambe Arum Kecamatan Puger - Wulandari , Maria Angela Indriasning; Dahliani, Yani; Jannah , Hofiatul; Ananta, Moh Dafit (Institut Teknologi dan Sains Mandala, 2022)
Tobacco has an important role in the socio-economic life of the community, such as the state in the form of tax revenues and foreign exchange earnings, employment, income of farmers, laborers, and traders, as well as income. But on the other hand, under the pretext of health, tobacco development and trade began to face opposition which was legalized through regulations. This has an impact on the sustainability of tobacco farming which in turn has an impact on the welfare of farmers. This paper aims to discuss the prospects and challenges faced by tobacco farmers in Kedung Sumur Hamlet, Jambe Arum Puger Village. In addition, tobacco farmers face problems: the marketing system in terms of branding, in terms of the capital side of the business. Alternative Problem solving: low-nicotine tobacco cultivation; diversification of derivative products; institutional optimization